LONGITUDINAL METHOD APPROACH IN ASSESSING THE MOLDOVAN MIGRANTS’ STOCK - Ștîrba, Vitalie; Crivenco, Andrei (Economy and Sociology, 2023)
Estimating international migration is a challenging exercise despite the information technologies used, regular censuses conducted, and available advanced administrative systems in collecting data on vital events. Recent works estimated the stocks and flows of Moldovan migrants mainly by using national administrative sources on population counts and data from the population censuses in the destination countries. This study aims to assess the stock of Moldovan migrants of the 1980–1995 birth cohorts, for which a longitudinal method was applied. Thus, were compared de facto population of the corresponding generations to their initial size (number of births), adjusting by survival rate. The results of the study show the existing stock of Moldovan migrants of the 1980–1995 year of birth and the impact of outmigration on the changes in the size of the corresponding cohorts as of 2016 and its trend until 2022. During the analysed period was emphasised a plateau in the migrants’ stock of the generations born in the early 1980s with a moderate return migration in the 2020–2022 period. On the other hand, the cohorts of the late 1980s and 1990s registered a significant increase in the number of migrants, which corresponds with the period of the entrance in high migration mobility ages. The study covers the entire territory of Moldova, including the left bank of the Nistru River and Bender municipality. The methodological part provides a complete description of the method applied, which might be further considered for estimating the migrants’ flows and stocks by using vital statistics or population census data.